Pentecostal theology"s problem (Pt 1 2:2): Maši ke phepa ke le nosi, selabe se tla le motsaya kgamelo – a Setswana proverb - Resane, Kelebogile T. (HTS teologiese studies, 2022)
Decolonisation of theology can be undertaken by engaging African proverbs and idioms. Pentecostalism, although the African Christian phenomenon is exploding, also needs to be decolonised in order to break itself of the western shackles of stereotyping Christianity as a western civilisation. The historical development of Pentecostalism, highlighting the heresies that invaded it, is examined, expanded and explained to support the notion that, indeed, the Setswana proverb: Maši ke phepa ke le nosi, selabe se tla le motsaya kgamelo, is a powerful tool to show that Pentecostal faith in its original form was unadulterated, but that the misunderstandings were brought along by certain Pentecostal teachers. The hermeneutical principle of inculturation is referred to as a way of justifying the usage of African proverbs in order to express and simplify theological concepts. Exegesis of 1 Peter 2:2 is undertaken to make an appeal that Pentecostal theology cannot be thrown out as it is a pure milk to be desired for spiritual maturity. This Petrine text is referred to as a basis that doctrinal purity within Pentecostalism should be a goal to be desired. The original Pentecostal initiative has been historically invaded and tinted by dissenting voices promoting some questionable beliefs and practices; however, its originality remains evangelically and fundamentally oriented.Contribution: This article contributes towards the journal’s vision of multidisciplinary theological perspective using hermeneutical studies and the literature to express the truth experienced in a context but embedded within a text. The article also contributes to the ongoing discourse on decolonisation of theology, especially within the Pentecostal Christianity.